CRYPTOSPORIDIOSIS: EPIDEMIOLOGI, PATOGENESIS, MANIFESTASI KLINIS, DIAGNOSIS, DAN PENATALAKSANAAN: TINJAUAN LITERATUR - Nur Bebi Ulfah Irawati; Luluk Hermawati; Silvia Fitrina Nasution; Putri Damayanti; Yuda Nabella Prameswari; Hilizza Awalina Zulfa (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
Cryptosporidiosis is a parasitic infection caused by protozoa of the Cryptosporidium genus that infect humans and animals worldwide. The disease remains a significant public health concern, particularly in regions with limited access to clean water and adequate sanitation. This study aimed to review recent scientific evidence regarding the epidemiology, pathogenesis, clinical manifestations, diagnosis, and management of cryptosporidiosis. A literature review method was employed by analyzing scientific articles published between 2015 and 2025 retrieved from databases including PubMed, Scopus and Google Scholar. Relevant studies were selected based on predefined inclusion criteria and analyzed narratively. The review indicates that Cryptosporidium hominis and Cryptosporidium parvum are the most common species causing human infection and account for the majority of cases worldwide. Transmission primarily occurs through the fecal–oral route via contaminated water or food, as well as direct contact with infected hosts. Infection involves parasite attachment and invasion of intestinal epithelial cells, leading to mucosal damage, malabsorption, and diarrhea. Clinical manifestations vary depending on the host's immune status, ranging from mild self-limiting diarrhea in immunocompetent individuals to severe and chronic infection in immunocompromised patients. Diagnosis is commonly established through microscopic detection of oocysts, antigen-based assays, and molecular methods such as polymerase chain reaction (PCR). Current management mainly focuses on supportive therapy, while nitazoxanide remains the only antiparasitic drug approved by the FDA for the treatment of cryptosporidiosis. Therefore, improvements in sanitation, development of diagnostic methods, and effective prevention strategies are essential to reduce the global burden of cryptosporidiosis.